Equilibrium Isotherm Studies on the Adsorption of Malachite Green and Lead Ion from Aqueous Solution Using Locally Activated Ugwaka Clay (Black Clay) - Asadu Christian Oluchukwu; Onoh Ikechukwu Maxwell; Agulanna Chibuzor Albert (Archives of Current Research International, 2018)
The efficiency of Malachite green dye and Lead ion removal from aqueous solution and industrial waste effluents by adsorption using activated clay made from Ugwaka clay (Black Clay) have been investigated. Pilot-scale activation of the clay was performed at a temperature of 100ºC for 1.5 hours with 3.0 M Phosphoric acid. The clay to acid ratio was 1:10 (w.w%). The results of the adsorption studies showed that activated clay produced from Ugwaka Clay is a good adsorbent. The adsorption data were analyzed using the Langmuir, Freundlich and Temkin model at different temperatures. The Freundlich isotherm model fitted best among the temperature variables, thereby signifying a monolayer adsorption. Statistical analysis conducted at 99% confidence level (P showed that the optimum conditions for the adsorption of the malachite green were 50ºC, 65 minutes, 0.60 g of adsorbent and pH 6.8, 45ºC, 35 minutes, 0.80 g of adsorbent and pH 2.35 for lead ion adsorption. The adsorption resulted in 90.57% and 89.7% removal of Malachite green dye and Lead ion respectively. The results of the effects of process parameters showed that they positively influenced the adsorption process.